Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien Pada Puskesmas Kota Jantho Aceh Besar - Faliza, Nur; Heriyana, Heriyana (PASAI, 2013)
This research aim  to know and analyse the influence of service quality consisted of reliability, responsiveness, confidence, emphaty and tangibles toward consumer satisfaction at puskesmas  Kota Jantho Aceh Besar and  the most dominant factor influence it. The data analysis method used in this study is multiple linear regression.The results showed that the variables reliability,responsiveness, confidence, emphaty and tangibles of the influance on  consumer satisfaction at Puskesmas Kota Jantho Aceh Besar, and  the dominant variable influancing consumer satisfaction is empathy.